'People just dae wit they can tae get by': Exploring the half-life of deindustrialisation in a Scottish community. Issue 2 (March 2023) - Clark, Andy
This article practically applies Sherry-Lee Linkon's 'half-life of deindustrialisation' thesis in examining a deindustrialising Scottish community. Linkon contends that, while the most visibly toxic impacts of deindustrialisation have dissipated over time, its lingering effects continue to cause harm in more subtle ways. Utilising qualitative research from a national study on the community impacts of organised crime, I consider the ways in which the long-term legacies of deindustrialisation and disinvestment manifest in the lived experiences of residents of Tunbrooke (pseudonym). I assess three areas where Linkon's half-life can be observed in Tunbrooke: the physical environment; poverty, addiction and mental ill-health; and external stigmatisation. I argue that, for those living in Tunbrooke, these processes shape their day-to-day lives, along with the omnipresent threat posed by organised crime and regular episodes of violence. However, rather than passively accepting this, there is opposition to the external view of the locality as 'a violent shithole', with an emphasis on the kinship and solidarity through adversity. I argue that the responses of Tunbrooke residents are framed through a lasting communal working-class identity, which has been strengthened as the area experienced the fallout of the half-life of deindustrialisation and the recent impacts of political austerity.